THE EFFECT OF EDUCATION POSTER ON NEW HABITS IN THE AGE OF COVID 19 ON KNOWLEDGE LEVEL OF THE ELDERLY AS A HIGH RISK GROUP (PRE EXPERIMENT STUDY) - Dewiyanti, Dewiyanti; Suaib, Maryam (Universitas Islam Negeri Alauddin Makassar, 2021)
The COVID-19 pandemic has become a pandemic that is able to close access to socialization, work and a decrease in people's economic income. Many people have died due to the COVID-19 virus. Elderly, is the age group that most of the victims in this case. Being infected with COVID-19 causes patients to experience shortness of breath, high fever, dry cough and weakness. The government is currently promoting the Adaptation of New Habits as an effort to prevent the transmission and increase of COVID-19 cases. When surveying 10 elderly people directly in the field in RT 004 and 003, the researchers found 7 elderly people who did not know about adapting new habits as a prevention effort and 3 other elderly people said they had heard from television broadcasts but could not explain well the description of adaptation of new habits. Therefore, the elderly need accurate and well-delivered information. One way to convey the right information to the elderly is to use health education with poster media. Poster media can contain information in a size that can be seen and understood by the elderly. The research will be conducted using the Pre-Experimental Design method with the One group pre and posttest design method using primary and secondary data which will be processed by the Wilcoxon test. The results of the study concluded that there was an effect of poster education about the new habits of the Covid 19 era on the level of knowledge of the elderly as a high risk group. Suggest for the elderly to continue to carry out strict health protocols until the pandemic period is over or resolved.